The Potential of Highland Tropical Wheat As an Object of Agroedutourism to Promote Tropical Wheat Development (Case Study in Wates Village, Getasan District, Semarang Regency) - Theresa Dwi Kurnia; Nugraheni Nugraheni Widyawati; Tinjung Mary Prihtanti (ASEAN Journal on Hospitality and Tourism, 2018)
Abstract. This study aims to know the potential of wheat farming in Getasan district as an object of agro edu-tourism and analyzed its development strategy to support tropical wheat production. Qualitative methods were used, with an interview with various tourism related stakeholders. The collected data were analyzed using the SWOT method. The results showed that wheat farming's in Getasan district have potentially to promote to be the object of agro edu-tourism. The study proposed several strategies, such as; Cooperation between tourism-related stakeholders; Involving local communities in promoting cultural resources in the region; Creating agro edu-tourism zones in various site; Plan an attractive and dynamic training program, special event, landscape arrangement, and promote it through various media channels; Improve managerial resources by establishing efficient structures, engaging in management training on agrotourism.